+0  
 
0
108
2
avatar

If \(g(x) = 2x^2+2x-1\), what is the value of \(g(g(2))\)?

 May 17, 2020
 #1
avatar+21955 
0

If  g(x)  =  2x2 + 2x -1,  find  g( g(2) ).

 

Work from the inside out; find the value of g(2).

    g(2)  =  2(2)2 + 2(2) - 1  =  11

 

Now, replace the g(2 of g( g(2) )  with 11,

so you now have  g( 11 )  =  2(11)2 + 2(11) - 1  =  263.

 

To summarize:  g( g(2) )  =  g( 11 )  =  263

 May 17, 2020
 #2
avatar+82 
+3

g(2) = 2(2^2) + 2(2) - 1 which equals 11. g(11) = 2(11^2) + 2(11) - 1 which is 263.

 May 17, 2020
edited by Mathlord  May 17, 2020

10 Online Users

avatar